Impact of Islamic Financial Inclusion on Economic Growth in Nigeria - Mairiga, Abubakar Ibrahim (International Journal of Islamic Economics and Governance, 2023)
Although the connection between finance and growth is well deliberated in literature, attentions are now geared to non interest inclusive finance with understanding the deficiency of traditional inclusive finance. However, the impact of interest free inclusive finance on growth still is partly examined. This research work dealt with Islamic inclusive finance - growth nexus. The research employed quarterly data spanning from (2010-2020). In this work, a novel index of Islamic financial inclusivity was constructed using the (PCA) and a recently developed Bootstrap ARDL (BARDL) Cointegration technique was used in analyzing the data. The finding indicates a number of results. First, the results of BARDL demonstrates a robust association among Islamic Inclusive finance and Growth. As such, it demonstrates the presence of positive and statistically significant nexus between Islamic inclusivity finance and growth. Moreover, findings also reveal presence of cointegration among Islamic inclusivity finance and growth. As such, interest free finance can be used as a tool to help nations to exit from economic recession and other macroeconomic challenges.